INTERPRETATION OF UNDER SURFACE STRUCTURE USING MAGNETIC METHODS IN MOUNTAIN AREA OF TANGKUBAN PERAHU AND THE SURROUNDING AREA - Lionard Kemit, Marchel
Research with magnetic methods was carried out to determine the distribution patterns of magnetic field anomalies used as estimates of geothermal anomalies. Data collection was carried out in the Tangkuban Perahu Mountain area and the village of Cikahuripan, Lembang District. Data retrieval was carried out on 23-30 August 2018 by using 2 sets of Proton Precession Magnetometer (PPM) with type G-856 that measured the total magnetic field size at 72 points determined in the study area. Data processing is done by IGRF correction and daily variation correction to get magnetic field anomaly values. Then reduction to poles and upward continuation is carried out to eliminate local anomalies to be processed in 2-dimensional and 3-dimensional modeling. Then the data is processed using Surfer, Magpick, Mag2DC, Oasis Montaj, and Matlab software. From the results of data processing, the total magnetic values obtained in the study area were between 43000 nT to 45800 nT, after being corrected anomalous magnetic field values were obtained between -1600 nT to 1200 nT. After modeling, 4 types of rocks were obtained in the study area of the first rock type with susceptibility values of 0.0000218 cgs or equivalent to 0.273808 SI with a depth of 0 m - 440 m is rock dominated by clay rock, the second type of rock with susceptibility value 0.0000334 cgs or equivalent with 0.419504 SI with a depth of 440 m - 960 m is a rock dominated by sandstone, the third type of rock with a susceptibility value of 0.0062351 cgs or equivalent to 78,314 SI with a depth of 960 m - 1350 m is a rock dominated by a mixture of basalt and diorite rocks and the fourth type of rock with a susceptibility value of 0.013438 or equivalent to 168.79 SI with a depth of 1350 m - 2000 m is a rock dominated by andesite rocks.